The Influence of Learning Styles on History Learning Outcomes Among Students of SMA Negeri 1 Bula - Wajo, Fitria; Wanci, Mahmudin; Warella, Rolina; Matitaputty, Jenny Koce; Sopacua, Jems (Universitas Syiah Kuala, 2023)
This study aims to determine how learning styles affect the history learning outcomes of students at SMA Negeri 1 Bula. The research used an ex post facto method with a quantitative approach to identify the cause-and-effect relationship between learning styles and student learning outcomes. The study was conducted at SMA Negeri 1 Bula from July to September 2022. Based on data analysis, it was found that there is a significant influence of students learning styles on their history learning outcomes. The correlation value obtained was 0.96, indicating a very strong relationship between the two variables. Furthermore, the coefficient of determination showed that learning styles contributed 92.16% of the influence on students history learning outcomes. Therefore, the alternative hypothesis (HI) is accepted, stating that learning styles positively affect history learning outcomes.